2017
DOI: 10.1186/s13027-017-0144-7
|View full text |Cite|
|
Sign up to set email alerts
|

Outcome of HIV-associated lymphoma in a resource-limited setting of Jos, Nigeria

Abstract: BackgroundLymphoma is a leading cause of cancer-related death among human immunodeficiency virus (HIV)-infected individuals in the current era of potent anti-retroviral therapy (ART). Globally, mortality after HIV-associated lymphoma has profound regional variation. Little is known about HIV-associated lymphoma mortality in Nigeria and other resource-limited setting in sub-Saharan Africa. Therefore, we evaluated the all-cause mortality after lymphoma and associated risk factors including HIV at the Jos Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(16 reference statements)
1
7
0
2
Order By: Relevance
“…The generally accepted cut-off for age according to IPI is 60-years [ 25 28 ]. We found that age ≥ 40 years was associated with a 2.5-fold increase in the hazards of death, which is similar to a study that was conducted in Nigeria [ 10 ]. Larger studies have provided conflicting results on the prognostic relevance of age categories which are below 60 years of age.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The generally accepted cut-off for age according to IPI is 60-years [ 25 28 ]. We found that age ≥ 40 years was associated with a 2.5-fold increase in the hazards of death, which is similar to a study that was conducted in Nigeria [ 10 ]. Larger studies have provided conflicting results on the prognostic relevance of age categories which are below 60 years of age.…”
Section: Discussionsupporting
confidence: 88%
“…Literature on the survival of African patients with lymphoma is steadily increasing. However, these studies included a relatively small number of HIV-infected patients (8–75) [ 6 10 ]. Notwithstanding, cohort studies of lymphoma patients in southern Africa report 12-month overall survival (OS) rates of 40–45% regardless of the treatment used [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normal BMI and completion of 6 or more cycles of chemotherapy were associated with favourable survival in our study. A retrospective study on HIV associated lymphomas in Nigeria reported stage of lymphoma as the only factor predictive of survival [ 24 ]. Other factors that have been noted to predict survival include type of lymphoma [ 25 ], age, ECOG performance scores, stage of lymphoma and LDH level [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normal BMI and completion of 6 or more cycles of chemotherapy were associated with favourable survival in our study. A retrospective study on HIV associated lymphomas in Nigeria reported stage of lymphoma as the only factor predictive of survival (27). Other factors that have been noted to predict survival include type of lymphoma (28), age, ECOG performance scores, stage of lymphoma and LDH level (29).…”
Section: Discussionmentioning
confidence: 99%